Verbs of Movement in the Poetry of Wafaa Jaabour: A Lexical-linguistic Approach (Diwan "and There Is No Shirt That Indicates Me" as a Model) - al-Bayyari, Murad Rafik (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aims to examine the actions of movement in the poetry of Wafa Ja'bour and elucidate how the poetess employs them in her poems. Furthermore, it aims to identify the connotations derived from the actions of movement in her poetry, leading to an understanding of the emotional states experienced by the poetess resulting from the use of these actions, ultimately exploring the temporal connotations of these actions. Methods: The descriptive-analytical approach is employed in studying the actions both lexicographically and semantically. The study follows a method that begins with examining the lexicographical meaning of the action of movement, followed by considering its temporal form, whether it is past, present, or imperative, as found in the collection "And There Is No Shirt That Points to Me." The actions are then classified according to types of movement, leading to an analysis of how the poetess employs the action in her collection. Results: The poetess extensively utilizes present tense actions of movement compared to past tense actions and imperative verbs. Most of the actions of movement in her poetry carry negative connotations in contrast to positive connotations. It was observed that the present tense verb often deviates from its morphological meaning to indicate a temporal meaning imposed by the context. Conclusion: The study of actions of movement in the poetess's collection reveals numerous emotional states experienced by her.